Kobieta walcząca o pozycję w polu produkcji artystycznej Samoidentyfikacja, samoorganizacja i samoemancypacja według Ewy Partum: - - Załuski, Tomasz (Zagadnienia Rodzajów Literackich, 2019)
Ewa Partum’s conceptual art of the early 1970s consisted in creating a new artistic language but at the same time it bore some traits of feminism and was marked by the figure of what might be called “the touch of a woman”. The artist’s self-organizational activities which took the form of establishing and running of an alternative art gallery called “Adres” can be also considered as self-emancipatory feminist practice. The gallery was instrumental in Partum’s attempts at producing symbolic capital for herself and taking a position in the field of Polish and international neo-avant-garde.